2002
DOI: 10.1021/jp014690k
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Pressure-Broadening Coefficients for the F‘ = 3 ← F‘ ‘ = 4 Hyperfine Line of the 2P1/22P3/2 Transition in Atomic Iodine

Abstract: We describe a series of measurements of pressure-broadening coefficients for the F′ ) 3 r F′′ ) 4 line of the 2 P 1/2 r 2 P 3/2 transition in atomic iodine. This is the optical transition of the chemically pumped atomic iodine laser (COIL), and our results are relevant to a more complete understanding of this important class of high-power lasers. The measurements were made in sealed cells using an argon ion laser to photodissociate molecular iodine and a tunable diode laser to probe directly the atomic transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The iodine absorption cross section used is corrected for the small amount of collisional broadening by using known broadening coefficients for He and O 2 . 28 The gases were delivered by calibrated mass flow controllers. The excimer laser dissociates approximately 10 À3 of the photolyte each shot, and the entire cell volume was refreshed every 4-5 shots at the 1 Hz repetition rate of the experiments.…”
Section: Determination Of Radical Absorption Cross Sectionsmentioning
confidence: 99%
“…The iodine absorption cross section used is corrected for the small amount of collisional broadening by using known broadening coefficients for He and O 2 . 28 The gases were delivered by calibrated mass flow controllers. The excimer laser dissociates approximately 10 À3 of the photolyte each shot, and the entire cell volume was refreshed every 4-5 shots at the 1 Hz repetition rate of the experiments.…”
Section: Determination Of Radical Absorption Cross Sectionsmentioning
confidence: 99%
“…For the line broadening of atomic iodine with He and O 2 at 296 K o T o 775 K, Davis et al reported n(He) ¼ 0.36 and n(O 2 ) ¼ 0.70 24. …”
mentioning
confidence: 99%
“…Comparison of the predicted (solid and dashed curves) and observed (circles) (a) HO2 (every 50th point shown for clarity) and (b) I (every 100th point shown) produced in the photodissociation of n-propyl iodide at 648 K obtained by infrared FM spectroscopy.The solid curve is obtained by using the present kinetic model (as depicted in Figures4 and 5), and the dashed curve is obtained by increasing the rate coefficients for I + RO 2 and I + HO2 by factors of 10 and 3, respectively. Observed I-atom concentrations are derived by using the absolute absorption cross section for the F* ) 3 r F ) 4 hyperfine transition of iodine atoms at 1.315 µm 39,40.…”
mentioning
confidence: 99%